DIGITALISASI PEMASARAN UMKM BUDIDAYA JAMUR MELALUI INTEGRASI GOOGLE MAPS DAN BRANDING VISUAL DI DESA KADUNUNGGAL KECAMATAN KALAPANUNGGAL KABUPATEN SUKABUMI - M. Retno Daru Dewi; Ahmad Hidayat (STISIP Widyapuri Mandiri Sukabumi, 2025)
This community service addresses the critical issue of limited market access and low digital visibility faced by the local Small and Medium Enterprise (UMKM) of mushroom cultivation in Kadununggal Village, Sukabumi Regency. Despite the high potential for production, the enterprise operated traditionally, lacking a digital footprint and clear visual branding. The primary objective of this project was to enhance the UMKM's capacity for market expansion through digital empowerment. The method employed was a participatory approach, consisting of direct consultation, branding design, and the technical implementation of digital tools, executed over one month (August 4 to August 27, 2025). The program resulted in two measurable outputs: the creation of a detailed Google Maps profile for the mushroom cultivation site, allowing external customers easy navigation and verification; and the provision and installation of a professional business banner (visual branding). These outputs successfully transformed the UMKM’s identity from a local offline business to one with crucial digital visibility. The implementation effectively provided the UMKM management with a foundational digital marketing tool, thereby overcoming the traditional marketing constraints and contributing directly to the enterprise's sustainability.